Dynamic emotion perception and prior expectancy. (June 2016) - Dzafic, Ilvana; Martin, Andrew K.; Hocking, Julia; Mowry, Bryan; Burianová, Hana
Abstract: Social interactions require the ability to rapidly perceive emotion from various incoming dynamic, multisensory cues. Prior expectations reduce incoming emotional information and direct attention to cues that are aligned with what is expected. Studies to date have investigated the prior expectancy effect using static emotional images, despite the fact that dynamic stimuli would represent greater ecological validity. The objective of the study was to create a novel functional magnetic resonance imaging (fMRI) paradigm to examine the influence of prior expectations on naturalistic emotion perception. For this purpose, we developed a dynamic emotion perception task, which consisted of audio-visual videos that carry emotional information congruent or incongruent with prior expectations. The results show that emotional congruency was associated with activity in prefrontal regions, amygdala, and putamen, whereas emotional incongruency was associated with activity in temporoparietal junction and mid-cingulate gyrus. Supported by the behavioural results, our findings suggest that prior expectations are reinforced after repeated experience and learning, whereas unexpected emotions may rely on fast change detection processes. The results from the current study are compatible with the notion that the ability to automatically detect unexpected changes in complex dynamic environments allows for adaptive behaviours in potentially advantageous or threatening situations. Highlights: We examine the influence of prior expectations on dynamic emotion perception. Novel fMRI task with emotional videos congruent/incongruent with emotional cues. Congruency associated with activity in prefrontal regions, amygdala and putamen. Incongruency associated with activity in temporoparietal junction and cingulate.